2019
DOI: 10.1073/pnas.1901655116
|View full text |Cite
|
Sign up to set email alerts
|

Bladder drug mirabegron exacerbates atherosclerosis through activation of brown fat-mediated lipolysis

Abstract: Mirabegron (Myrbetriq) is a β3-adrenoreceptor agonist approved for treating overactive bladder syndrome in human patients. This drug can activate brown adipose tissue (BAT) in adult humans and rodents through the β3-adrenoreceptor-mediated sympathetic activation. However, the effect of the mirabegron, approved by the US Food and Drug Administration, on atherosclerosis-related cardiovascular disease is unknown. Here, we show that the clinical dose of mirabegron-induced BAT activation and browning of white adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…Its integrity is essential to procure anti-atherogenic effects of thermogenic AT [ 13 ]. This suggests that BAT and wBAT stimulation by cold exposure or β3-adrenoreceptor agonists may lead to the same pro-atherosclerotic impact seen in previous studies conducted in the similar mouse model [ 105 , 106 , 107 ]. Thus, the browning process is a potential and non-negligible risk factor for the 1 in 250 people with this disease [ 120 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Its integrity is essential to procure anti-atherogenic effects of thermogenic AT [ 13 ]. This suggests that BAT and wBAT stimulation by cold exposure or β3-adrenoreceptor agonists may lead to the same pro-atherosclerotic impact seen in previous studies conducted in the similar mouse model [ 105 , 106 , 107 ]. Thus, the browning process is a potential and non-negligible risk factor for the 1 in 250 people with this disease [ 120 ].…”
Section: Discussionsupporting
confidence: 64%
“…However, the same cold condition was beneficial for the lipidic profile of wild-type mice and decreased atherogenesis [ 106 ]. Another recent study reported increased atherosclerosis development in Apoe −/− and Ldlr −/− mice treated with a β3-adrenoceptor agonist [ 107 ]. Both the Apoe −/− and Ldlr −/− mice showed reduced clearance of triglycerides-rich apolipoprotein remnants by the liver.…”
Section: Atherosclerosismentioning
confidence: 99%
“…In addition, GPCRs have high medical relevance because they constitute the major target of currently available drugs (Hauser et al, 2017). Since systemic stimulation of cAMP signaling via beta2-and beta3-adrenergic receptors (beta2-and beta3-AR) is associated with significant cardiovascular side effects including hypertension and atherosclerosis (Cypess et al, 2015;Sui et al, 2019), the identification of alternative pathways is not only of biological interest, but also has translational potential.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of YM-178 to mice for 4-6 weeks at similar dosage to this study (i.e. 0.8mg/kg) reduces fat mass, increases UCP1 in IWAT and glucose uptake in BAT at standard housing temperature (SHT) whilst driving atherosclerosis, through BAT lipolysis in ApoE-/- and LdlR-/- mice [32]. Here, we show YM-178 treatment in obese animals raised at thermoneutraility has no impact on thermogenesis although it does modulate specific proteins involved in cell differentiation and skeletal muscle contraction.…”
Section: Discussionmentioning
confidence: 99%